Stereoselective synthesis of beta-C-Allyl- and beta-C-propargyl-D-arabinofuranosides - Ramana, C. V.; Narute, Sachin B.; Gonnade, Rajesh G.; Patil, Rahul S. (Synthesis-Stuttgart, 2008)
The stereoselective synthesis of beta-configured C-allyl- and C-propargyl-D-arabinofuranosides (4,7-anhydro-1,2,3-deoxy-D-gluco-oct-1-enitols and -oct-1-ynitols) was addressed by employing allylation/propargylation of a dialdofuranose under aqueous Barbier reaction conditions and acid-catalyzed furan ring transposition of 5-O-mesyl-manno-oct-7-eno- or 5-O-mesyl-manno-oct-7-ynofuranoside derivatives.
Keywords: Allylation; Barbier reaction; C-glycoside; D-mannose; propargylation; Ring transposition

Stereospecific synthesis of C-arabinofuranosides and carba-disaccharide analogues of Motif C of cell wall AG complex of Mtb - Patil, Rahul S.; Ahire, Ketan M.; Ramana, C. V. (Tetrahedron Letters, 2012)
A simple strategy for the synthesis of alpha- and beta-C-arabinofuranosides featuring a furan ring transposition reaction has been developed. A novel double furan ring transposition reaction has proposed and executed for the synthesis of the carba-disaccharide analogue of Motif C of the cell wall AG complex of Mtb. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Arabinose; C-Glycosides; Carba-disaccharide; Cell wall AG complex; Ring transposition